Estrogen Promotes Endometrial Cancer Development by Modulating ZNF626, SLK, and RFWD3 Gene Expression and Inducing Immune Inflammatory Changes - Fan, Jiuming; Zhang, Mengyao; Wu, Huailiang; Ye, Zehua; Wang, Liyan (Biomedicines, 2025)
: Elevated estrogen has been found to contribute to the pathological development of endometrial cancer (EC), potentially through alterations in the tumor inflammatory immune microenvironment. However, the exact mechanisms underlying this process remain unclear. : Bioinformatics was used to identify differentially expressed genes, analyze pathway enrichment, and assess their correlation with immune cell infiltration. Ishikawa cells and ECC-1 cells were stimulated with estradiol (E2) or the selective estrogen receptor modulator Arzoxifene, and qPCR was performed to measure gene expression changes. CCK8 and FACS assays were used to analyze cell cycle alterations, while Western blotting (WB) was used to evaluate apoptosis. : ZNF626 and SLK were highly expressed in EC tissues, whereas RFWD3 expression was downregulated. Immune cell infiltration analysis revealed a positive correlation between ZNF626 and M2 macrophages, while SLK was negatively correlated with M1 macrophages, memory B cells, and plasma cells. RFWD3 showed more complex correlations with multiple immune cell phenotypes, including T cells. E2 stimulation resulted in the increased expression of ZNF626 and SLK, while RFWD3 expression decreased. This was accompanied by enhanced cell proliferation and suppressed apoptosis. In contrast, Arzoxifene stimulation produced the opposite effects. : Estrogen promotes cell proliferation and inhibits apoptosis by upregulating ZNF626 and SLK, while downregulating RFWD3. Furthermore, estrogen induces a shift in the tumor microenvironment, characterized by a reduction in memory CD4+ T cells and a transition from M1 to M2 macrophage phenotypes, thus facilitating the onset and progression of EC.